2012
DOI: 10.1124/jpet.112.194506
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effects of Nicotinic Partial Agonists Varenicline and Sazetidine-A in Murine Acute and Tonic Pain Models

Abstract: Nicotinic agonists display a wide-range profile of antinociceptive activity in acute, tonic, and chronic pain models. However, their effectiveness is limited by their unacceptable side effects. We investigated the antinociceptive effects of two new ␣4␤2* nicotinic partial agonists, varenicline and sazetidine-A, in acute thermal and tonic pain mouse models. Both drugs failed to induce significant effects in the tail-flick and hot-plate tests after subcutaneous administration. However, they blocked nicotine's ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
3
29
0
1
Order By: Relevance
“…Our results showed that the nicotine and sazetidine anti-nociceptive effects were fully dependent on α 5 subunits in both phases I and II of the formalin test. These results along with our recent report [16], suggest that the antinociceptive effects of nicotine and sazetidine-A in the formalin test appears to be mediated largely by α 4 α 5 β 2 *-nAChRs subtypes. In contrast, α 5 *-nAChRs subtypes do not mediate the effects of varenicline in the same test.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results showed that the nicotine and sazetidine anti-nociceptive effects were fully dependent on α 5 subunits in both phases I and II of the formalin test. These results along with our recent report [16], suggest that the antinociceptive effects of nicotine and sazetidine-A in the formalin test appears to be mediated largely by α 4 α 5 β 2 *-nAChRs subtypes. In contrast, α 5 *-nAChRs subtypes do not mediate the effects of varenicline in the same test.…”
Section: Discussionsupporting
confidence: 83%
“…These active doses were selected based on our recent report in the same test [16]. All behavioral testing on WT and KO animals in this study was performed in a blinded manner.…”
Section: Methodsmentioning
confidence: 99%
“…47-50, 52, 63-69 The results from these studies are highly supportive of our proposal to develop novel nicotinic therapeutics based on their ability to selectively desensitize α4β2 nA-ChRs. In the present study, we investigated the agonist and desensitization properties of these new analogs at human α4β2 nAChRs and rat α3β4 nAChRs (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…In studies using nAChR agonists and antagonists as well as mice with nAChR subunits null mutations, researchers have shown that nAChRs containing α3, α4, α5, α6, α7, β2, and β4 subunits are involved in modulating nocifensive behaviors in response to acute noxious thermal stimuli (Damaj et al, 2007; Damaj et al, 1999; Marubio et al, 1999) and in response to inflammatory and neuropathic processes (AlSharari et al, 2012; Bagdas et al, 2015; Damaj et al, 1999; Freitas et al, 2015; Saika et al, 2015; Wieskopf et al, 2015; Xanthos et al, 2015; Yalcin et al, 2011). Others have also shown that mice with null mutations of α4, α5, or β2 have decreased response to the analgesic effects of nicotine, but intact response to the antinociceptive effects of morphine (Damaj et al, 2007; Marubio et al, 1999).…”
Section: Discussionmentioning
confidence: 99%